PENGARUH KETEPATAN WAKTU PENGEMBALIAN REKAM MEDIS RAWAT INAP TERHADAP EFEKTIVITAS PELAYANAN REKAM MEDIS - annisa ulfah; Julia Santika (INFOKES (Informasi Kesehatan), 2022)
The accuracy of retrieval medical records is very important to the process of health services in hospitals. The purpose of this study was to determine the effect of timeliness of retrieval inpatient medical records to the effectiveness of medical record service at Rumah Sakit TK IV 03.07.04 Guntur Garut. The research method used quantitative methods with a descriptive correlational approach and data processing using SPSS version 25 program. The data collection techniques using observation, questionnaires, and literature study. This study used a simple random sampling technique with a sample of 86 medical records and 16 officers. Based on the results of the study, the effect of the timeliness of retrieval inpatient medical records on the effectiveness of medical record service at Rumah Sakit TK IV 03.07.04 Guntur Garut is 55%. The problems that often arise is Lack of socialization regarding Standard Prosedur Operating in retrieval of medical records of inpatients, and the length of time doctors complete patient medical records and the absence of Standard Service Minimum. Suggestions for the hospital are to socialize and remind doctors and other medical professions when meeting about the accuracy of returning medical record files to be more disciplined in completing medical record files in accordance with Standard Prosedur Operating policies so that the return of medical record files does not experience delays and Standard Service Minimum is held for targets performance achievemen.Keywords: Timeliness of Retrieval, Medical Record